Cardiac manifestations of PRKAG2 mutation - Pooya Banankhah; Gregory A. Fishbein; Anthony Dota; Reza Ardehali (BMC, 2018)
Abstract Background The Protein Kinase AMP-Activated Non-Catalytic Subunit Gamma 2 (PRKAG2) cardiac syndrome is characterized by glycogen accumulation in the cardiac tissue. The disease presents clinically with hypertrophic cardiomyopathy (HCM), and it is often associated with conduction abnormalities. Case presentation A 23 year-old female with history of Wolff-Parkinson-White (WPW) and HCM presented for evaluation after an episode of Non-ST Elevation Myocardial Infarction (NSTEMI). The patient was found to have severe coronary bridging on angiography and underwent an unroofing of the left anterior descending artery (LAD). Due to the constellation of symptoms, the patient underwent genetic testing and a cardiac muscle biopsy. Genetic testing was significant for an Arg302Gln mutation in the PRKAG2 gene. Cardiac tissue biopsy revealed significant myocyte hypertrophy and large vacuoles with glycogen stores. Conclusion The pathologic and genetics findings of our patient are consistent with PRKAG2 syndrome. Patients presenting with conduction abnormalities and suspected HCM should be considered for genetic testing to identify possible underlying genetic etiologies.